Serotonin levels in the dorsal raphe nuclei of both chipmunks and mice are enhanced by long photoperiod, but brain dopamine level response to photoperiod is species-specific. (23rd April 2015) - Goda, Ryosei; Otsuka, Tsuyoshi; Iwamoto, Ayaka; Kawai, Misato; Shibata, Satomi; Furuse, Mitsuhiro; Yasuo, Shinobu
Highlights: Long photoperiod upregulated serotonin levels in the raphe of mice and chipmunks. Daylength differentially altered the brain dopaminergic system in mice and chipmunks. C57BL/6J mice may be a useful model of the brain serotonergic system in SAD. Abstract: Seasonal affective disorder (SAD) is a subtype of major depressive or bipolar disorders associated with the shortened photoperiod in winter. This depressive disorder is integrally tied to the seasonal regulation of the brain's serotonergic system. Recently, we found that C57BL/6J mice subjected to a forced-swim test exhibited immobility, a photoperiod-dependent depression-associated behavior, and suppression of brain serotonin levels. However, mice are nocturnal animals, and it is unclear whether the brain serotonergic system responds similarly to photoperiod in nocturnal and diurnal species. This study compared the responses of brain serotonergic and dopaminergic systems to photoperiod in diurnal chipmunks and nocturnal C57BL/6J mice. In both species, serotonin levels in the dorsal raphe nuclei were higher under long-day conditions than short-day conditions, suggesting a similarity in the photoperiod responses of the serotonergic systems. However, photoperiod affected dopamine levels in various brain regions differently in the two species. Some chipmunk brain regions exhibited stronger photoperiod-induced changes in dopamine levels than those of C57BL/6J mice, and the direction of the changes in the hypothalamus was opposite. In conclusion, photoperiod may regulate the brain serotonergic system through similar mechanisms, regardless of whether the animals are diurnal or nocturnal, but photoperiod-dependent regulation of brain dopamine is species-specific.